Assessment of protective effects of Celastrus paniculatus seed extract against MPP+ induced damage in SH - SY5Ycells (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
In the Indian system of traditional medicine, Celastrus paniculatus seeds and oil have been recognized for their therapeutic efficacy in treating cognitive dysfunctions. This study unveils the protective effect of Celastrus paniculatus seed extract (CPME) against the neurotoxin 1-methyl - 4-phenlypyridinium (MPP+) induced damage in SH-SY5Y human neuroblastoma cell line. The protective effect of CPME was assessed by MTT assay by pretreating the SH-SY5Y cells with CPME at two different concentrations (10 and 25 µg/mL) prior to MPP+ exposure (250µM) and the percentage of viable cells was determined. Significant improvement in cell viability was observed with CPME pretreatment and the effect was well pronounced at 25µg/mL concentration. In addition, MPP+ treated cells with or without CPME pretreatment were analyzed for apoptotic cell death by different staining techniques like acridine orange/ethidium bromide (AO/EB), propidium iodide (PI) and 4’ 6 - diamidino - 2 - phenyl indoledihydrochloride (DAPI). Same way, changes in the mitochondrial membrane potential and intracellular ROS production were assessed by staining respectively with rhodamine 123 and 2’, 7’ - dichlorofluorescin diacetate (DCFDA). Quercetin served as a positive control in this study. Observations recorded in fluorescence microscopic image analysis indicated that pre - treatment with CPME caused appreciable protective effects against MPP+ induced cell death by alleviating apoptotic changes such as cell shrinkage, condensation/fragmentation of nuclear material along with restoring ROS levels and mitochondrial membrane potential. Altogether, results from this study points to the protective effects of CPME against MPP+ induced cell death by regulating the cellular production of ROS.